Standardisation of an indirect enzyme-linked immunosorbent assay for the detection - Manuela Tittarelli; Barbara Bonfini; Fabrizio De Massis; Armando Giovannini; Massimo Scacchia (Veterinaria Italiana, 2011)
An indirect enzyme-linked immunosorbent assay (ELISA) was evaluated for the detection of Brucella antibodies in milk from water buffalo (Bubalus bubalis Linnaeus, 1758). The test accuracy was evaluated on milk samples from the Campania Region in Italy. A total of 100 negative samples were collected from 10 officially brucellosis-free herds in Salerno Province, while 30 positive samples were collected from 3 herds in Caserta Province, where animals gave positive results to the official tests and it was here that Brucella abortus biovar 1 had been isolated. Test sensitivity was 100%, with a confidence interval (CI) of 90.8%-100%, while specificity was 98% (CI 93%-99.4%) on individual milk samples. To simulate bulk milk samples from herds infected at various levels of infection, dilutions from 1:10 to 1:100 of positive milk samples in negative milk were also used. The probability of detecting antibodies in positive milk samples was higher than 50% up to a dilution of 1:50 in negative milk. Considering the average national water buffalo herd size, the probability of identifying infection in a water buffalo herd by bulk milk testing is 50% (CI 33.1%-66.9%) in the worst case scenario of a single infected animal contributing to the bulk milk.